Enhanced cyclability of Li–O2 batteries with cathodes of Ir and MnO2 supported on well-defined TiN arrays. Issue 6 (26th January 2018) - Leng, Limin; Li, Jing; Zeng, Xiaoyuan; Tian, Xinlong; Song, Huiyu; Cui, Zhimin; Shu, Ting; Wang, Haishui; Ren, Jianwei; Liao, Shijun
Abstract : Enhanced cyclability of Li–O2 batteries with cathodes of Ir and MnO2 supported on well-defined TiN arrays. Abstract : The cycling stability of Li–O2 batteries has been impeded by the lack of high-efficiency, and durable oxygen cathodes for the oxygen-reduction reaction (ORR) and the oxygen-evolution reaction (OER). Herein we report a novel TiN nanorod array-based cathode, which was firstly prepared by growing a TiN nanorod array on carbon paper (CP), and then followed by depositing MnO2 ultrathin sheets or Ir nanoparticles on the TiN nanorods to form well-ordered, three-dimensional (3D), and free-standing structured cathodes: TiN@MnO2 /CP and TiN@Ir/CP. Both cathodes exhibited good specific capacity and excellent cycling stability. Their specific discharge capacities were up to 2637 and 2530 mA h g −1, respectively. After 200 cycles for 2000 h at a current density of 100 mA g −1, no obvious decays were observed for TiN@MnO2 /CP and TiN@Ir/CP cathodes, while significant decreases were observed after the 80 th and 30 th cycles for the Pt/C and TiN/CP cathodes, respectively. Such high performance can be ascribed to the 3D array structure with enough microspace and high surface area, which facilitated the high dispersion of active components and prevented the formation of large/irreversible Li2 O2 .